2019
DOI: 10.3324/haematol.2018.209478
|View full text |Cite
|
Sign up to set email alerts
|

Serendipity: decitabine monotherapy induced complete molecular response in a 77-year-old patient with acute promyelocytic leukemia

Abstract: Acute promyelocytic leukemia (APL) is an uncommon but very aggressive subtype of acute myeloid leukemia (AML), accounting for 10-15% of adult AML with 600-800 new cases per year in the United States. 1,2 Over 95% of cases involve translocation t(15;17)(q22;q21), which results in the promyelocytic leukemia retinoic acid receptor alpha (PML-RARa) rearrangement and fusion protein. 3 Most of the remaining APL cases harbor a fusion protein involving RARa and another partner. 4 The PML-RARa fusion gene initiates APL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…Interestingly, Liu et al reported a novel HNRNPC-RARA fusion in APL lacking PML-RARA rearrangement, sensitive to venetoclax-based therapy. Moreover, Abboud et al demonstrated that decitabine may be an efficacious and more tolerable alternative to elderly patient with low-risk AP therapy (13). The results give us some hints; combination therapy with venetoclax and decitabine may show a promising clinical efficacy in variant APLs.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Liu et al reported a novel HNRNPC-RARA fusion in APL lacking PML-RARA rearrangement, sensitive to venetoclax-based therapy. Moreover, Abboud et al demonstrated that decitabine may be an efficacious and more tolerable alternative to elderly patient with low-risk AP therapy (13). The results give us some hints; combination therapy with venetoclax and decitabine may show a promising clinical efficacy in variant APLs.…”
Section: Discussionmentioning
confidence: 99%